UJI AKTIVITAS ANTIBAKTERI EKSTRAK KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP BAKTERI Staphylococcus epidermidis - Iva Juliyanti; Maulita Saraswati; Estuningtyas Ayu Hapsari (Universitas An Nuur, 2024)
Background: Red dragon fruit skin has many benefits, but currently the utilization of red dragon fruit skin has not been carried out optimally so that it becomes environmental waste. One of the benefits is as an antibacterial because it contains flavonoids, alkaloids, saponins, and tannins. Purpose: To determine the potential of red dragon fruit peel extract in inhibiting bacterial growth against Staphylococcus epidermidis bacteria. Method: Red dragon fruit peel was macerated with 70% ethanol, characterized by specific parameters and nonspecific parameters and tested for antibacterial activity using the disc method with concentrations of 10%, 20%, and 40%, then the results of the antibacterial data obtained were tested by oneway-Anova analysis and Post Hoc Tukey. Results: The yield results obtained were 10.66%, dark brown in color, sour smell, sticky and thick texture. Red dragon fruit peel extract contains flavonoids, alkaloids, tannins, saponins, and phenols. The extract is free from ethanol. The moisture content of the powder was found to be 9.85±0.057. Specific gravity 0.956±0.006. Bacterial test results obtained 10% concentration 4.1mm, 20% concentration 8.1mm, 40% concentration 16mm, positive control 31.2mm. The results of data analysis are significant at 0.000, and each concentration has a significant difference. Conclusion: Red dragon fruit peel extract has antibacterial activity against Staphylococcus epidermidis